Therapeutic potential of the MDM2 inhibitor Nutlin-3 in counteracting SARS-CoV-2 infection of the eye through p53 activation - Zauli, Giorgio; AlHilali, Sara; Al-Swailem, Samar; Secchiero, Paola; Voltan, Rebecca (Frontiers in Medicine, 2022)
Starting from the beginning of the severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) global pandemic, most of the published data has concentrated on the respiratory signs and symptoms of Covid-19 infection, underestimating the presence and importance of ocular manifestations, such as conjunctivitis, usually reported in SARS-CoV-2 infected patients. With the present review we intend to resume the ocular involvement in SARS-CoV-2 infection and the recent discoveries about the different cell types and tissues of the eye that can be directly infected by SARS-CoV-2 and propagate the infection. Moreover, reviewing literature data about p53 expression in normal and diseased eye tissues, we hypothesize that the pleiotropic protein p53 present at high levels in cornea, conjunctiva and tear film might play a protective role against SARS-CoV-2 infection. Since p53 can be easily up-regulated by using small molecule non-genotoxic inhibitors of MDM2, we propose that topical use of Nutlin-3, the prototype member of MDM2 inhibitors, might protect the anterior surface of the eye from SARS-CoV-2 infection, reducing the spreading of the virus.